Enhancing financial literacy and citizenship as pillars of social and economic sustainability in Baubau city - Slamet Agus; Salam Safrin; Hasyim Bahmid; Narti Narti; Zarina Zarina; Putri Erin Amalia; Amalia Waode Abadina; Hezradian Rahma Fathan; Hezraria Rahmi Fathan (BIO Web of Conferences)
Social and economic sustainability in the digital era depends on preparing the younger generation with essential competencies, particularly in financial literacy and civic awareness. Despite national efforts to improve financial education, many primary school students in Indonesia still struggle with basic financial skills, including managing money wisely and distinguishing real from counterfeit currency. This study aims to enhance both financial and civic literacy among elementary school students in Baubau City as foundational pillars for long-term social and economic development. Employing a mixed-method approach, the research combines quantitative surveys and qualitative observations, covering stages of needs analysis, program design, and evaluation of learning outcomes. A total of 100 students participated in pre- and post-intervention assessments. The results indicate a significant improvement—on average, 40–45%—in students’ understanding of financial concepts and civic responsibilities. These outcomes highlight the importance of integrating financial and citizenship education into the primary school curriculum to foster early awareness, responsible behavior, and cultural rootedness. The study provides evidence that targeted interventions at the basic education level can contribute meaningfully to sustainable development. It also reveals an existing gap in financial and civic competence that must be addressed by educators and policymakers through more responsive and inclusive curriculum design.